Islamic Law and Copyright In Academic World: The Dynamic Debates between Privatization and Distribution of Knowledge (Mazahib, 2018)
The article explores copyright problem dynamic in a globalized academic world, especially in the Muslim worlds. The discussed issue in this paper is a conflict of interest between knowledge privatization and distribution, and its relation to the Islamic norms. This paper argues that the main problem of the concept is that the discourse is dominated by the idea of knowledge privatization by the publishers as capitalists, supported by the Government through the policy represented in Copyright law. This study finds that there are several movements emerged in response to the development of copyright law. At least, there are two stream movements; anti copyright movement and movement which demand copyright reform. By presenting examples of copyright resistance movements in the academic world such as Sci-Hub, Libgen, A2K movement, and some copyright experiences in the Muslim world, this article will be guided by Foucauldian genealogical discourse theory. This article confirms that the interests of publishers and academic interests are two things that are difficult to discuss in order to achieve a win win solution. While copyright laws favor the ruling interests of things, it does not fully effective in handling the legal cases on academic and non-profit matters. Besides, Islamic law has its own ambivalence to the copyright case. On the one hand, Islam advocates the widespread dissemination of knowledge, but on the other hand the Muslim worlds have to limit the spread of the sciences in accordance with the interests of intellectual property rights.Keywords: Intellectual Property right, Islam and copyright, privatization of knowledge.